PERSEPSI MASYARAKAT TERHADAP KENAIKAN TARIF PARKIR DAN JALAN BERBAYAR ELEKTRONIK DI JAKARTA - Harminto, Randhito Satrio (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The development of tourism in Indonesia is currently being promoted as one of the industries that can increase the Impact of the Increase in Parking Rates in the Revised Pergub 31/2017 on the Acceleration of the Implementation of JBE in Jakarta. JBE and the policy of increasing parking rates are expected to be able to control volume and obtain funds to build public transportation. Knowing the effect of increasing parking rates in Jakarta on the implementation of JBE in Jakarta. In this study, a survey method will be used by creating a questionnaire as a research tool that will be given to users of public and private rental transportation and fellow drivers, or both. And use the Statistical Package for Social Sciences (SPSS) application to test normality, test validity and test reliability.